Solve the initial value problem y"+3y'=0; y(0)=3, y'(0)=6.
The characteristic equation is
"k^2+3k=0 \\\\\nk(k+3)=0 \\implies k_1=0, k_2=-3."
We have two real distinct roots, then the general solution is
"y(t)=C_1e^{0t}+C_2e^{-3t}=C_1+C_2e^{-3t}."
Note that "y'(t)=-3C_2e^{-3t}."
Applying the initial conditions gives the following system of equations for the coefficients "C_1, C_2" :
"3=y(0)=C_1+C_2, \\quad (1)\\\\\n6=y'(0)=-3C_2 \\implies C_2=-2."
From (1): "C_1=3-C_2=3-(-2)=5".
We get the solution "y(t)=5-2e^{-3t}."
Comments
Leave a comment